Protease-activated receptor-1 negatively regulates proliferation of neural stem/progenitor cells derived from the hippocampal dentate gyrus of the adult mouse - Masayuki Tanaka; Masanori Yoneyama; Tatsuo Shiba; Taro Yamaguchi; Kiyokazu Ogita (Elsevier, 2016)
Thrombin-activated protease-activated receptor (PAR)-1 regulates the proliferation of neural cells following brain injury. To elucidate the involvement of PAR-1 in the neurogenesis that occurs in the adult hippocampus, we examined whether PAR-1 regulated the proliferation of neural stem/progenitor cells (NPCs) derived from the murine hippocampal dentate gyrus. NPC cultures expressed PAR-1 protein and mRNA encoding all subtypes of PAR. Direct exposure of the cells to thrombin dramatically attenuated the cell proliferation without causing cell damage. This thrombin-induced attenuation was almost completely abolished by the PAR antagonist RWJ 56110, as well as by dabigatran and 4-(2-aminoethyl)benzenesulfonyl fluoride (AEBSF), which are selective and non-selective thrombin inhibitors, respectively. Expectedly, the PAR-1 agonist peptide (AP) SFLLR-NH2 also attenuated the cell proliferation. The cell proliferation was not affected by the PAR-1 negative control peptide RLLFT-NH2, which is an inactive peptide for PAR-1. Independently, we determined the effect of in vivo treatment with AEBSF or AP on hippocampal neurogenesis in the adult mouse. The administration of AEBSF, but not that of AP, significantly increased the number of newly-generated cells in the hippocampal subgranular zone. These data suggest that PAR-1 negatively regulated adult neurogenesis in the hippocampus by inhibiting the proliferative activity of the NPCs.